Diversity of Actinomycetes at Several Forest Types in Wanagama I Yogyakarta and Their Potency as a Producer of Antifungal Compound - Reni Nurjasmi; Jaka Widada; N. Ngadiman (Indonesian Journal of Biotechnology, 2009)
Actinomycetes are bacterial groups that produce many secondary metabolites, which different biological activities, such as antifungi, antibacteria, antivirus, antitumor, etc. Actinomycetes are widely distributed in soil and their diversity is influenced by type of forest. The aim of this study is to investigate diversity of actinomycetes in several forest types of Wanagama I forest in Yogyakarta and their potency as a producer of antifungal compound. Soil samples under the forest of Tectona grandis, Swietenia macrophylla King, Bamboosa vulgaris, Melaleuca leucadendron, and Gliricidia maculata were used as sources of soil bacteria. Bacteria and actinomycetes communities were analyzed through culture-independent approach by RISA and nested-PCR RISA using actinomycetes spesific primer (F243), respectively. Through culture-dependent approach, isolated actinomycetes diversity were analyzed by identification of morphology (colony and cell), genetic (BOX element by rep-PCR), and secondary metabolites (thin layer chromatography). In addition, isolates were assayed for their antifungal activity against Saccharomyces cerevisae, Candida albicans, Fusarium oxysporum and Aspergillus flavus. The presence of Polyketide Synthase-I (PKS-I) and NonRibosomal Peptide Synthetase (NRPS) genes were amplified by PCR to study their correlation with antifungal activity of the actinomycete isolates. The results showed that types of forest influence diversity of rhizobacteria especially actinomycetes. According to culture-independent approach, relatively, com- munity of rhizobacteria from the highest were soil under the forest of B. vulgaris, G. maculata, T. grandis, S.macrophylla King, and M. leucadendron, respectively. Meanwhile, community of actinomycetes from the highest were soil under the forest of G. maculata, B. vulgaris, M. leucadendron, S. macrophylla King, and T. grandis, respec- tively. Fourty-three morphologically different isolates were found by using culture-dependent approach consisting of 17 isolates were found in soil under the forest of M. leucadedron, each of 9 isolates in G. maculata and T. grandis, 6 isolates in S. macrophylla King. and 2 isolates in B. vulgaris. More diversity of secondary metabolites were observed in soil actinomycetes under the forest of M. leucadendron. Of the 43 isolates, 100% were active against S.cerevisae, 37.20% against C. albicans, 95.30% against F. oxysporum, and 83.70% against A. flavus. Antifungal activity of actinomycete isolates did not always have correlation with the presence of PKS-I and NRPS.